Reservoirs of P and fertilizer with technology on the path to sustainability in coffee production - Siman, Felipe Cunha; Andrade, Felipe Vaz; Stauffer, Eduardo; Mendonça, Eduardo de Sá (Frontiers in Sustainable Food Systems, 2024)
Phosphorus (P) is found in the soil in organic (Po) and inorganic (Pi) forms and in compartments with different lability, normally being separated into labile, moderately labile, restricted lability and non-labile forms. The different sources of fertilizers used in the long term may change the form and availability of P over time, increasing or not its availability to plants, which can positively influence coffee productivity. This work aimed to evaluate in the field the effects of phosphate fertilizers with associated technology on the availability of P in soil with high P adsorption capacity after successive fertilizations in Coffea canephora Pierre ex A.Froehner crop. In the experiment, three phosphate sources (conventional MAP – MAP, polymer-coated MAP – MAPPOL and MAP + filter cake – MAPTF); two doses (100 and 150 % of the recommendation); and two nitrogen sources (conventional urea – UC and urea coated with polymer and sulfur – UPS) were used. After 3 years of field experimentation, the soil was collected at a depth of 0–10 cm and then, the labile, moderately labile, and restricted lability fractions were determined. Phosphate fertilizers with associated technology obtained better results in relation to MAP in terms of Pi and Po contents for the labile compartment over time, with an average increase of 66.02 mg dm−3 P in the soil. For the moderately labile fraction, fertilizers with associated technology increased the Pi content (HCl 1M) in the soil in relation to MAP, by 2.56 mg dm−3, representing an increase of 37.92%. These compartments are considered an important reserve of available P for crops grown in soils with high adsorption capacity. Phosphate fertilizers with integrated protection (MAPPOL + MAPTF) compared to MAP increased productivity by 6.79 and 11.62 % in the 2017/2018 and 2018/2019 harvests, respectively. Phosphate fertilizers with associated technology promote P dynamics in different soil compartments, increasing Coffea canephora Pierre ex A. Froehner productivity and sustainability.